Analysis of Success Factors for One Single ERP (Enterprise Resource Planning) Implementation (Case Study of Soe Holding) - Ariq Qorihatunnasik; Syti Sarah Maesaroh; Muhammad Rizki Nugraha (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research examines the implementation of One Single ERP system in SOE Holding, which previously faced challenges in consolidating data from three State-Owned Enterprises (SOEs) with different ERP systems. This research uses the ADKAR framework (Awareness, Desire, Knowledge, Ability, Reinforcement) to manage organizational change, overcome cultural and business process differences, and minimize resistance. The result of this research is that Employee Readiness requires a large allocation of effort to improve employee readiness through training, mentoring, and reinforcement. Top Management Support is also important to ensure strategic support and policies are aligned with transformation goals. Not all factors have an equal influence on successful implementation. With limited resources, Holding needs to prioritize the most influential factors, such as Employee Readiness and Top Management Support, so that efforts can be focused effectively and increase the chances of success. This approach accelerates the ERP implementation process while minimizing risks so that digital transformation goals can be achieved more quickly and efficiently.